Risk-Adjusted Values, Timing of Uncertainty Resolution, and the Measurement of Project Worth - Bernhard, Richard H. (Journal of Financial and Quantitative Analysis, 1984)
Richard H. Bernhard, Risk-Adjusted Values, Timing of Uncertainty Resolution, and the Measurement of Project Worth, The Journal of Financial and Quantitative Analysis, Vol. 19, No. 1 (Mar., 1984), pp. 83-99